2002
DOI: 10.1111/j.1365-2621.2002.tb08829.x
|View full text |Cite
|
Sign up to set email alerts
|

Inulin and Sugar Contents in Helianthus tuberosus and Cichorium intybus Tubers: Effect of Postharvest Storage Temperature

Abstract: Inulin, sucrose, fructose, and glucose contents in tubers of Helianthus tuberosus (Jerusalem artichoke) and Cichorium intybus stored at different temperatures (-18, 4, and 18°C) after harvesting were followed. Inulin content in both tubers decreased during storage. In C. intybus this decrease was associated with increases in glucose and fructose contents. In H. tuberosus the fructan fraction having molecular weight between 800 and 1200 increased after sucrose reached its maximum content [1.3·10 -1 g (g d.w.) -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 12 publications
(9 reference statements)
4
19
0
Order By: Relevance
“…Our results show relatively low level of inulin in Jerusalem artichoke tubers. It could be influenced by genetic potential and different temperatures during storage (Cabezas et al, 2002), while inulin content also depends on the extracting technical conditions (Lingyun et al, 2007). Inulin content obtained in our samples is similar to inulin content in the chicory root which can contain up to 20% of storage carbohydrates, mainly inulin (Baert et al, 1992).…”
Section: Resultsmentioning
confidence: 60%
“…Our results show relatively low level of inulin in Jerusalem artichoke tubers. It could be influenced by genetic potential and different temperatures during storage (Cabezas et al, 2002), while inulin content also depends on the extracting technical conditions (Lingyun et al, 2007). Inulin content obtained in our samples is similar to inulin content in the chicory root which can contain up to 20% of storage carbohydrates, mainly inulin (Baert et al, 1992).…”
Section: Resultsmentioning
confidence: 60%
“…Storage of tubers promotes the degradation of inulin to an extent that depends on the storage conditions. It has been also reported that inulin is degraded by an internal enzyme, inulase, during storage (Cabezas, Rabert, Bravo, & Shene, 2002;Modler, Jones, & Mazza, 1993); therefore, primary processing soon after harvest will be required in order to maintain a high content of inulin; e.g., heat treatment at or above 60°C has been reported to inactivate inulase. Jerusalem artichokes have unwanted aromatic flavours that discourage daily consumption, also the development of blackening of the tubers as a result of oxidation occurs while processing, thus appropriate primary processing was surmised in this study to solve these problems.…”
Section: Introductionmentioning
confidence: 98%
“…Among these substrates, inulin has rec eived a major interest since it is present as a carbohydrate reserve in a large variety of plant roots and tubers such (Cabezas et al, 2002;Singh and Bhermi, 2008).…”
Section: Introductionmentioning
confidence: 99%